Digital diplomacy on Facebook - example of the Embassy of the Russian Federation and the Embassy of the Kingdom of the Netherlands - Gajić, Draga; Milinkov, Smiljana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
Diplomacy has faced numerous challenges and transformations in the last ten years, especially during the coronavirus pandemic. Even outside academic circles, terms such as digital diplomacy, virtual diplomacy, cyber diplomacy, e-diplomacy, hybrid diplomacy, and Zoom diplomacy can be read or heard more often. The goal of the research is to determine how the embassies of the Russian Federation and the Kingdom of the Netherlands (in Bosnia and Herzegovina and the Republic of Serbia) use the social network Facebook as a platform for promoting their own foreign policy goals, but also topics such as gender equality and the fight against gender-based violence. Quantitative- qualitative content analysis was used as a research method. A total of 54 posts published by the official Facebook pages of the embassies from November 25, 2023 until 10.12.2023. during the global campaign, 16 Days of Activism against Gender-based Violence were analyzed. The Embassy of the Kingdom of the Netherlands in the Republic of Serbia and the Republic of Montenegro had the most posts (31), and the Embassy of the Kingdom of the Netherlands in Bosnia and Herzegovina and the Embassy of the Russian Federation in the Republic of Serbia had the fewest posts (each had four). The Embassy of the Kingdom of the Netherlands in the Republic of Serbia and the Republic of Montenegro had the most posts about the campaign 16 Days of Activism against Gender-based Violence. The other analyzed embassies did not have any posts related to gender-based violence or the campaign 16 Days of Activism against Gender-based Violence.